Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2002
DOI: 10.1128/iai.70.7.3611-3620.2002
|View full text |Cite
|
Sign up to set email alerts
|

Expression of thePlasmodium falciparumImmunodominant Epitope (NANP)4on the Surface ofSalmonella entericaUsing the Autotransporter MisL

Abstract: Gram-negative bacterial proteins which are exported from the cytosol to the external environment by the type V secretion system are also known as autotransporters. Once translocated to the periplasmic compartment by the sec-dependent general secretory pathway, their C-terminal domain forms a pore through which the N-terminal domain travels to the outer membrane without the need of other accessory proteins. MisL (protein of membrane insertion and secretion) is a protein of unknown function located in the pathog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
44
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(46 citation statements)
references
References 36 publications
2
44
0
Order By: Relevance
“…Recently, use of E. coli outer membrane protein TolC for surface display of protective listerial B-and T-cell epitopes in a Salmonella vaccine strain has been shown to be efficacious in vivo (46). In summary, autotransporters facilitate effective surface display of antigenic determinants on live Salmonella vaccine carriers, leading to humoral (42) and cellular immune responses in vivo (29). This study demonstrated that surface display of a Helicobacter antigen via the AIDA-I autotransporter can induce protective immune responses.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Recently, use of E. coli outer membrane protein TolC for surface display of protective listerial B-and T-cell epitopes in a Salmonella vaccine strain has been shown to be efficacious in vivo (46). In summary, autotransporters facilitate effective surface display of antigenic determinants on live Salmonella vaccine carriers, leading to humoral (42) and cellular immune responses in vivo (29). This study demonstrated that surface display of a Helicobacter antigen via the AIDA-I autotransporter can induce protective immune responses.…”
Section: Discussionmentioning
confidence: 93%
“…Humoral immune responses have been observed after vaccination of mice with attenuated Salmonella strains with immunogenic determinants exposed on their surfaces by means of outer membrane proteins from E. coli, like OmpA (17), PhoE (24,47), LamB (6,18,32), and P87 fimbriae (7), the ice-nucleating protein from Pseudomonas aeruginosa (33), the main flagellar component FliC from Salmonella (9,40,40), or the Salmonella autotransporter MisL (42). Recently, use of E. coli outer membrane protein TolC for surface display of protective listerial B-and T-cell epitopes in a Salmonella vaccine strain has been shown to be efficacious in vivo (46).…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, experiments with recombinant Ty800 in the nasal murine model were not previously reported, while plasmid stability was observed in both Ty21a (16) and CVD908-htrA (27). The instability of L1S plasmids in CVD908-htrA may be linked to the presence of a constitutive promoter in our plasmids instead of the in vivo-inducible nirB promoter, which was generally used in other recombinant CVD908-htrA strains (27,44,50).…”
mentioning
confidence: 82%
“…The MisL C-terminal translocator domain can be used to display foreign antigens and elicits specific antibody responses in mice (30,31,36). Mice infected with serotype Typhimurium seroconvert to MisL, which provides indirect evidence for in vivo expression of this autotransporter protein (5).…”
mentioning
confidence: 99%